PROFILE AND FINANCIAL PERFORMANCE ANALYSIS OF THE COMPANY IN THE COAL MINING SECTOR OF PT.ADARO MINERAL TBK AS ONE OF THE COMPANIES LISTED UNDER THE IDX (INDONESIA STOCK EXCHANGE) - Likdanawati; Lisa Dwi Yana; Nailul Authar; Alya Azhara; Safrina (RADJA PUBLIKA, 2023)
The purpose of this study is to find out and analyze how the profile and financial performance of one of the mining sector companies PT. Adaro Mineral.Tbk which is listed on the IDX (Indonesian Stock Exchange). The main object of this research is PT. Adaro Mineral.Tbk. This study uses descriptive qualitative techniques and literature review. The results of this study are PT. Adaro Minerals Indonesia Tbk has increased in all aspects, including finance, but it is still said to be not good because the calculation results show that the company's ratio is still below the industry standard.